Baricitinib for the treatment of COVID-19 - Firdha Aprillia Wardhani; Syafika, Devina Sarah; Kusumaningrum, Yunita Dyah; Adelia Firandi (Faculty of Pharmacy, University of Jember, 2024)
Baricitinib which is one of the therapies for rheumatoid arthritis is a JAK inhibitor. WHO recommended therapy with the combination of baricitinib and corticosteroids in COVID-19 patients with severe or critical condition. Effectivity and safety assessment of Baricitinib use were carried out by reviewing the literature published between December 2019 – February 2022, and showed that the use of Baricitinib in COVID-19 patients resulted in an improvement of lung function, improvement of oxygen saturation, higher recovery rate, and lower mortality, with similar adverse event incidence. A loading dose or a higher dose can be recommended for patient with caution and consideration of higher possibility in the incidence of adverse events